Effect of reducing saturated fat intake on cardiovascular disease in adults: an umbrella review - Aramburu, Adolfo; Dolores-Maldonado, Gandy; Curi-Quinto, Katherine; Cueva, Karen; Alvarado-Gamarra, Giancarlo; Alcalá-Marcos, Katherine; Celis, Carlos R.; Lanata, Claudio F. (Frontiers in Public Health, 2024)
Introduction Our objective was to explore the effect of the reduction of saturated fat (SAF) intake on cardiovascular disease, mortality and other health-related outcomes in adults. Methods We conducted an umbrella review, searching Medline, Scopus, EMBASE, Cochrane Library, and LILACS databases for systematic reviews from December 1, 2012, to December 1, 2022. We have included meta-analyses of randomized controlled trials (RCTs) and cohort studies. We extracted effect sizes (95%CI), heterogeneity (I2), and evidence quality rating based on the population, intervention, comparator, and outcomes. Results 21 meta-analyses were included (three were from RCTs, and 18 were from cohort studies). Among meta-analyses of RCTs, 15 of the 45 associations were significant. The effect of reduction in SAF intake on combined cardiovascular events (RR 0.79, 95%CI 0.66–0.93) was graded as having moderate certainty of evidence. We found no effect on all-cause mortality, cardiovascular mortality, cancer deaths, and other cardiovascular events. Among meta-analyses of cohort studies, five of the 19 associations were significant. There was an increase in coronary heart disease mortality (HR 1.10, 95% CI 1.01–1.21) and breast cancer mortality (HR 1.51, 95% CI 1.09–2.09) in participants with higher SFA intake compared to reduced SFA. We found no effect on all-cause mortality, cardiovascular mortality, and other cardiovascular events. Conclusion This umbrella review found the reduction in SAF intake probably reduces cardiovascular events and other health outcomes. However, it has little or no effect on cardiovascular mortality and mortality from other causes. More high-quality clinical trials with long-term follow-up are needed. Systematic review registration: CRD42022380859.